Fractional Order Systems: Optimization, Control, Circuit Realizations and Applications - Taher Azar, Ahmad; Radwan, Ahmed G; Vaidyanathan, Sundarapandian (Advances in nonlinear dynamics and chaos (ANDC), 2018)
'Fractional Order Systems' consists of 21 contributed chapters by subject experts. Chapters offer practical solutions and novel methods for recent research problems in the multidisciplinary applications of fractional order systems, such as FPGA, circuits, memristors, control algorithms, photovoltaic systems, robot manipulators, oscillators, etc. The book is ideal for researchers working in the modeling and applications of both continuous-time and discrete-time dynamics and chaotic systems.